KARAKTERISASI OPTIK EKSTRAK BAYAM MERAH (RED AMARANTH) UNTUK APLIKASI DYE SENSITIZED SOLAR CELL (DSSC) - Vita Efelina; Endah Purwanti; Farradina Choria Suci; Arnisa Stefanie; Reni Rahmadewi (Sekolah Tinggi Teknologi Wastukancana, 2020)
We report how the prepare red amaranth extract. In this study, red amaranth extract was made using the maceration method. Energy is one of the basic needs for human life. One alternative to overcome the electricity crisis is the use of solar energy. Development of solar cells continues, until now many researchers are modifying basic materials using dyes commonly called Dye Sensitized Solar Cells (DSSC). This DSSC has great potential to be developed. Dyes commonly used as doping are synthetic and natural dyes. In this study using red spinach or red amaranth because red spinach has a pigment that can be used to substitute for synthetic colors. So far there has been no in-depth study examining the optical properties of the dye red amaranth extract material. Therefore, this research has carried out a study of the fundamental optical properties of the dye red amaranth extract material. Red amaranth extract caracterized by UV Vis and FTIR spectroscopy. Red amaranth absorbance occurs at wavelength of 432 nm and 663 nm.